Hubungan Antara Resiliensi dengan Peran Ibu Pada Anak Penyintas Bencana di Hutan Lere - Gustina (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2022)
This study departs from the assumption that in order for survivors to rise from stress, they need support from their families, especially mothers, in increasing the resilience of survivors. The formulation of the problem from this research is how is the relationship between resilience and the role of mothers in disaster survivors in Lere Huntara. The method used in this thesis research is a quantitative research method, using data collection techniques through questionnaires or questionnaires as data collection techniques. This research was conducted at Lere Huntara. The population in this study were children who survived the disaster in Lere Huntara with the criteria for children who were in the age range of 7-12 years and domiciled in Lere Village, West Palu District, Palu City. The collected data was then analyzed by testing the validity, reliability testing, and testing assumptions using SPSS 16 for Windows assistance techniques. The results obtained based on the results of statistical data analysis obtained a value of Tcount 1.609 < Ttable 1.687 and has a significant value (sig) 0.117 in the Coefficients table with a value of (significant level) 0.05, meaning 0.117 > 0.05 then it can be interpreted that there is no there is a significant correlation between resilience and the role of mothers in Child Survivors in the Lere Huntara. Another finding of this study is based on the results of interviews conducted by researchers that in general the child survivors in Lere Huntara are not cared for by their parents.